THE IMPORTANCE OF MODERN TECHNOLOGIES, INNOVATIVE PROGRAMS AND SYSTEMS IN EDUCATION (American Journal of Interdisciplinary Research and Development, 2024)
This article discusses various programs used in teaching schoolers and students , their role in the organization of lessons, and new digital systems In education.